Neighbors and extension agents in Ethiopia: who matters more for technology adoption? - Krishnan, P; Patnam, M (Oxford University Press, 2013)
The increased adoption of fertilizer and improved seeds are two key aspects to raising the level of land productivity in Ethiopian agriculture. However, the adoption and diffusion of such technologies has been slow. We use data from Ethiopia between 1999–2009 to examine the role of learning from extension agents versus learning from neighbors for both improved seeds and fertilizer adoption. We combine farmers' spatial networks with panel data to identify these influences, and find that while the initial impact of extension agents was high, the effect wore off after some time, in contrast to learning from neighbors.